Unraveling the Essence of Crime in International Criminal Law: A Review of Iryna Marchuk’s Work - Amandha, Asyaffa Ridzqi (International Law Discourse in Southeast Asia, 2023)
This review encapsulates the essence of Iryna Marchuk's seminal work, "The Fundamental Concept of Crime in International Criminal Law," published by Springer and spanning 311 pages, with ISBN 978-3-642-28245-4. Hailing from Copenhagen, Denmark, Marchuk's book navigates the intricate terrain of international criminal law with precision and scholarly insight. Marchuk's examination centers on unraveling the foundational notion of crime within the expansive realm of international law. Through a meticulous exploration of legal precedents, theoretical frameworks, and contemporary challenges, she illuminates the multifaceted dimensions of criminality in a global context. The book embarks on a journey through the evolution of international criminal law, tracing its origins and milestones while dissecting the complexities inherent in defining and prosecuting crimes of international concern. Marchuk's analysis delves into the intersection of legal principles and moral imperatives, probing the intricate balance between state sovereignty and universal human rights. Furthermore, Marchuk scrutinizes the jurisprudence of international tribunals and courts, dissecting landmark cases and seminal judgments to discern overarching trends and emerging jurisprudential principles. Through this lens, she evaluates the efficacy of existing legal frameworks in addressing grave crimes such as genocide, war crimes, and crimes against humanity. Marchuk's work also confronts the challenges of enforcement and accountability in the international arena, interrogating the mechanisms for ensuring compliance and prosecuting perpetrators across borders. By interrogating the evolving nature of transnational crimes and the shifting dynamics of global governance, she offers valuable insights into the imperative for international cooperation and collaboration in the pursuit of justice.